(untitled) (BIRDEM Medical Journal, 2020)
Paraneoplastic limbic encephalitis is a multifocal inflammatory disorder of the central nervous system (CNS) that is associated with remote neoplasm. The most common malignancy associated with it is bronchial carcinoma, typically small cell carcinoma of the lung but it has also been reported to happen with squamous cell lung carcinoma. Paraneoplastic limbic encephalitis should be considered as differential diagnosis in any patient with known malignancy who presents with altered behavior, involuntary movement of body or dementia. Here, we present a case of a 62-year-old male who presented as paraneoplastic encephalitis with squamous cell lung carcinoma. Birdem Med J 2020; 10(2): 133-136